The immunogenicity problem in antibody therapy - Waldmann, Herman (Henry Stewart Talks, 2019)
Features of an immunogenic antibody, Processing of immunoglobulin antibodies, Strategies for overcoming immunogenicity, Tolerisation vs. Immunisation, Elimination of the immunogenicity of therapeutic antibodies, Immunogenicity/Tolerogenicity of mutant antibodies, Application/Incorporation of tolerance-inducing properties